Acute inflammatory edema as a variant of pseudocellulitis resolved after transcatheter aortic valve implantation - Shalabi, Mojahed Mohammad K.; Dacy, Nicole N.; Grimwood, Ronald E.; Fiala, Katherine; Amenell, Meredith (Proceedings - Baylor University. Medical Center, 2022)
Acute inflammatory edema is a noninfectious inflammatory condition of the skin that is commonly seen in critically ill patients. It is characterized by edematous, erythematous, and nontender plaques involving the abdomen and thighs, sparing areas of the skin subject to pressure. Risk factors include fluid overload, hypoalbuminemia, and obesity. Differentiating acute inflammatory edema from cellulitis can be challenging. Supportive care is the mainstay therapy for acute inflammatory edema, with interventions primarily focused on lowering the fluid burden. We report an unusual case of a nonobese patient in the outpatient setting with acute inflammatory edema.